PENGARUH PROSES REKRUTMEN DAN SELEKSI TERHADAP KINERJA KARYAWAN MENGGUNAKAN REGRESI LINIER BERGANDA - Rohmah, Dillah Dalillatur; Wilandari, Angestika (LPPM Universitas Nusa Mandiri, 2023)
KOPPOSINDO (Indonesian Postal Employees Cooperative) One of the functions of the service sector in Central Jakarta City is supervising the management of reserve and credit funds, as well as administering KBM rentals. The aim of this research is to determine the extent to which the recruitment process affects the productivity of KOPPOSINDO (Indonesian Postal Employees Cooperative) workers. Distributing questionnaires is the main method of data collection in this research. A total of 37 respondents were included in this research sample. This research uses a quantitative approach with sampling using saturated sampling. IBM SPSS version 25 was used for this test. In addition to the assumptions of validity, reliability, normality, multicollinearity, and heteroscedasticity, multiple regression, t test, F test, and R-squared test were applied to the findings. The results of this research indicate that the attitude variable has a negative influence on employee performance, but the impact is small. Employee performance is influenced by factors related to recruitment, selection and performance evaluation at the same time.